Deciphering the Multi-Chromosomal Mitochondrial Genome of Populus simonii - Bi, Changwei; Qu, Yanshu; Hou, Jing; Wu, Kai; Ye, Ning; Yin, Tongming (Frontiers in Plant Science, 2022)
Mitochondria, inherited maternally, are energy metabolism organelles that generate most of the chemical energy needed to power cellular various biochemical reactions. Deciphering mitochondrial genome (mitogenome) is important for elucidating vital activities of species. The complete chloroplast (cp) and nuclear genome sequences of Populus simonii (P. simonii) have been reported, but there has been little progress in its mitogenome. Here, we assemble the complete P. simonii mitogenome into three circular-mapping molecules (lengths 312.5, 283, and 186 kb) with the total length of 781.5 kb. All three molecules of the P. simonii mitogenome had protein-coding capability. Whole-genome alignment analyses of four Populus species revealed the fission of poplar mitogenome in P. simonii. Comparative repeat analyses of four Populus mitogenomes showed that there were no repeats longer than 350 bp in Populus mitogenomes, contributing to the stability of genome sizes and gene contents in the genus Populus. As the first reported multi-circular mitogenome in Populus, this study of P. simonii mitogenome are imperative for better elucidating their biological functions, replication and recombination mechanisms, and their unique evolutionary trajectories in Populus.